Effect of a high-heat-capacity mattress topper on sleep in elite badminton players during a summer training period: Does 1 size fit all? - Chauvineau, M.; Hollville, E.; Duforez, F.; Guilhem, G.; Nedelec, M. (International Journal of Sports Physiology and Performance, 2025)
Purpose: Inadequate sleep quantity or quality is common in elite athletes and may worsen with high summer temperatures. High-heat-capacity bedding systems have demonstrated beneficial effects on several sleep parameters. The present study evaluated the effect of a high-heat-capacity mattress topper (HMT) on sleep quantity and quality in elite badminton players during a summer training period.